Accordance of William Morris Davis Theory with the Landscapes of the Earth Surface - Khairandish, Gulistan; Anwari, Shirkhan (Technium Social Sciences Journal, 2021)
The natural surface views of the earth's surface are actually like the broken mosaics that formed the earth's crust. The surface of the earth is composed of different views, which is has been existed due to different internal and external forces of the earth's crust, such as destructive operations of the earth's surface, terrestrial operations, orogenic operations, folds, protrusions and number of processes that cause changes in the Earth's crust. The complexities of natural landscapes are greater than the simple buildings and flatness of the surface those collectively introduce the features of the surface. Landscapes are usually better explained by understanding the factors that cause them, because each of the terrestrial landscapes are remnants of various geomorphological factors that cannot be easily identified and need further investigation. William Morris Davis is an American geomorphologist who was the first to offer a general view of the Earth's appearance.